Development of a Needs Scale for Nurses Receiving In-Service Palliative Care Education. Issue 3 (May 2016) - Chang, Hui-Ju; Hsu, Li-Ling; Hsieh, Suh-Ing; Chu, Tsung-Lan; Yu, Wen-Pin
Abstract : Background: Nurses play pivotal roles on palliative care teams and are able to spend more time with patients and their families than are other healthcare professionals. As a consequence, assessing the needs for palliative care education in connection with in-service classes for nurses is clearly extremely important and can help in the planning of appropriate palliative care classes to enhance the quality of care. Objectives: The goals of this study were to investigate the content needs of nurses with regard to a palliative care in-service education program and to perform exploratory factor analysis on those needs. Methods: This study used a cross-sectional questionnaire survey. A total of 614 questionnaires were distributed, and 600 valid questionnaires were returned (97.72%). Data analysis was performed by means of descriptive statistics, reliability analysis, factor analysis, and Pearson correlation. Results: The 6 factors discovered by exploratory factor analysis were handling of pain and symptoms, ethical issues concerning terminal patients, hospice preparation and care, the concept of palliative care, communication and counseling, and cultural and spiritual factors, which together explained 77.22% of the variance. Conclusion: The results of this study shed light on the program needs for in-service education about palliative care and the 6 factors most associated with those needs. Implications for Practice: In order to realize the whole-person concept of care, future efforts should target the planning of palliative care in-service education programs, strengthening of nurse training, coordination of administrative resources, and interteam cooperation.